Pengembangan Media Pembelajaran Matematika Interaktif Berbasis Konstruktivisme Untuk Siswa SMA Kelas X Pada Materi Jarak Pada Bangun Ruang - Lusi Englita (Journal on Education, 2021)
Visualization capabilities is a very important skill in mathematics learning. Having a better visualization capabilities students will understand the subject matter well, particularly in geometry material as the material within the geometry. But the fact that the school found that the visualization capabilities of students is still low. One effort to improve visualization upon ability students is to develop media based interactive mathematics constructivism. The purpose of this development is to produce a valid instructional media, practical and effective. This development research uses a Plomp model consisting of three phases namely: preliminary, prototyping, and assessment. Subjects were students of class X SMAN 1 Koto XI Tarusan. The results of validity of media based interactive learning constructivist mathematics have valid criteria in content and construct. Media Learning has met the criteria of practical because it can be done well in learning activities. Media effective learning has met the criteria for being able to increase the activity of student learning and mastery learning outcomes over a predetermined classical completeness. Thus, it can be concluded that the media based interactive learning constructivist mathematics was valid, practical and effective.